Global change impacts on large-scale biogeographic patterns of marine organisms on Atlantic oceanic islands. (January 2018) - Ávila, Sérgio P.; Cordeiro, Ricardo; Madeira, Patrícia; Silva, Luís; Medeiros, António; Rebelo, Ana C.; Melo, Carlos; Neto, Ana I.; Haroun, Ricardo; Monteiro, António; Rijsdijk, Kenneth; Johnson, Markes E.
Abstract: Past climate changes provide important clues for advancement of studies on current global change biology. We have tested large-scale biogeographic patterns through four marine groups from twelve Atlantic Ocean archipelagos and searched for patterns between species richness/endemism and littoral area, age, isolation, latitude and mean annual sea-surface temperatures. Species richness is strongly correlated with littoral area. Two reinforcing effects take place during glacial episodes: i) species richness is expected to decrease (in comparison with interglacial periods) due to the local disappearance of sandy/muddy-associated species; ii) because littoral area is minimal during glacial episodes, area per se induces a decrease on species richness (by extirpation/extinction of marine species) as well as affecting speciation rates. Maximum speciation rates are expected to occur during the interglacial periods, whereas immigration rates are expected to be higher at the LGM. Finally, sea-level changes are a paramount factor influencing marine biodiversity of animals and plants living on oceanic islands. Highlights: We tested large-scale biogeographic patterns on 4 marine groups in 12 Atlantic Ocean archipelagos. Species richness is strongly correlated with littoral area. Species richness decreases during glacial episodes, in comparison with interglacial periods. Maximum speciation rates are expected to occur during interglacial periods. Sea-level changes are a paramount factor influencing marine biodiversity around oceanic islands.